METODE DAKWAH USTADZ DALAM MENINGKATKAN MINAT SHALAT BERJAMAAH PEMUDA DI PASAR ONAN MANDUAMAS - sarkawi, sarkawi; Sri Sultan Hamengkubono, Sri Sultan Hamengkubono (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2022)
Islam as a religion which from the mere mention of its name reflects a promise to its adherents in the form of safety, of course in its expansion it requires the participation of da'wah activists. Whether it's called preachers, preachers, scholars, clerics and so on. In introducing Islam, the da'i need the ability to support their da'wah activities so that the message conveyed can be understood and accepted by the recipient of the da'wah (mad'u). Da'wah is one of the obligations of a Muslim. This da'wah is delivered using a method that is in accordance with the conditions of the congregation being preached. In communication science, da'wah methods are often known as approaches, namely the ways in which a preacher or communicator to achieve a certain goal on the basis of wisdom and compassion. The da'wah activities carried out by Ustadz at the Nurul Huda Mosque in Pasar Onan Manduamas village were an increase in community worship, especially in congregational prayers at the mosque. The methods used include the lecture method, discussion method, and the formation of Islamic organizations. This type of research is qualitative focused on the applied da'wah as well as the inhibiting and supporting factors when applying the da'wah method. Data collection techniques through observation (observation), interviews and documentation. Data analysis techniques in this study are data reduction, data presentation and conclusion drawing. The results showed that the ustad's da'wah method in increasing youth's interest in praying together had two factors, namely the supporting factors and supporting factors for the implementation of the ustad's da'wah method in increasing interest in praying in congregation at the mosque by forming associations through the formation of Islamic organizations such as the GP Organization. Ansor and NU fatayats that directly involve young people and women, while the inhibiting factors for the ustadz's da'wah method in increasing interest in praying together with youth in mosques are the lack of knowledge about religion, especially worship and the influence of the community environment as well as the distance to places of worship which is far enough to make youth and the community less interested to pray in congregation and perform other worship activities in the mosqu